The role of tumor microenvironment in collective tumor cell invasion. (May 2017) - Wu, Jia-shun; Sheng, Su-rui; Liang, Xin-hua; Tang, Ya-ling
For many cancer types, cancer cells invade into surrounding tissues by collective movement of cell groups that remain connected via cell–cell junctions. This migration is completely distinguished from single-cell migration, in which cancer cells disrupt the tight intercellular junctions and gain a mesenchymal phenotype. Recently, emerging evidence has revealed that collective cell invasion depends on not only cell-intrinsic mechanisms but also on extracellular mechanisms by bidirectional interplay between the tumor cell and the tumor environment. Herein, in this review we discuss the role and underline mechanisms of tumor microenvironment in collective tumor cell invasion, particularly focusing on extracellular matrix remodeling and cross-talk between tumor and stromal cells.